Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(x+18\) = 6 - 2\(x\)
\(x\) + 2\(x\) = 18 - 6
3\(x\) = 12
\(x\) = 4
b, 17 - \(x\) = 7 - 6\(x\)
- \(x\) + 6\(x\) = 7 - 17
5\(x\) = - 10
\(x\) = - 2
c, \(x\) + 15 = 20 - 4\(x\)
\(x\) + 4\(x\) = 20 - 15
5\(x\) = 5
\(x\) = 1
d, 7\(x\) - 4 = 20 + 3\(x\)
7\(x-3x=20+4\)
4\(x\) = 24
\(x\) = 6
e, -12 + \(x\) = 5\(x\) - 20
-12 + 20 = 5\(x\) - \(x\)
4\(x\) = 8
\(x\) = 2
f, 4\(x\) - 18 = \(x\) + 27
4\(x\) - \(x\) = 27 + 18
3\(x\) = 45
\(x\) = 15
Mình làm 5 câu thôi nhé !:
1) \(7^x\cdot49=7^{90}\)
\(\Rightarrow7^x\cdot7^2=7^{90}\)
\(\Rightarrow7^{x+2}=7^{90}\)
\(\Rightarrow x=90-2\)
\(\Rightarrow x=88\)
2) \(2^x\cdot4=128\)
\(\Rightarrow2^x\cdot2^2=2^7\)
\(\Rightarrow2^{x+2}=2^7\)
\(\Rightarrow x=7-2\)
\(\Rightarrow x=5\)
3) \(3^x-1=2^4\cdot5\)
\(\Rightarrow3^x=80+1\)
\(\Rightarrow3^x=81\)
\(\Rightarrow3^x=3^4\)
\(\Rightarrow x=4\)
4) \(3^x+15=42\)
\(\Rightarrow3^x=42-15\)
\(\Rightarrow3^x=27\)
\(\Rightarrow3^x=3^3\)
\(\Rightarrow x=3\)
5) \(4\cdot2^x-3=125\)
\(\Rightarrow2^2\cdot2^x=128\)
\(\Rightarrow2^{x+2}=2^7\)
\(\Rightarrow x=7-2\)
\(\Rightarrow x=5\)
6)
\(5^x=5^{15}:5^3\\ \Leftrightarrow5^x=5^{15-3}\\ \Leftrightarrow5^x=5^{12}\\ \Leftrightarrow x=12\)
7)
\(4^x=4^{15}:16\\ \Leftrightarrow4^x=4^{15}:4^2\\ \Leftrightarrow4^x=4^{15-2}\\ 4^x=4^{13}\\ \Leftrightarrow x=13\)
8)
\(7^x=7^{20}:7^{10}\\ \Leftrightarrow7^x=7^{20-10}\\ \Leftrightarrow7^x=7^{10}\\ \Leftrightarrow x=10\)
9)
\(11^x=11^{11}:11\\ \Leftrightarrow11^x=11^{11-1}\\ \Leftrightarrow11^x=11^{10}\\ \Leftrightarrow x=10\)
10)
\(3^{15}.3^x=3^{30}\\ \Leftrightarrow3^x=3^{30}:3^{15}\\ 3^x=3^{30-15}\\ \Leftrightarrow3^x=3^{15}\\ \Leftrightarrow x=15\)
a. -12 + x = 5x - 20
<=> 4x = 8
<=> x = 2
b. 7x - 4 = 20 + 3x
<=> 4x = 24
<=> x = 6
c. 5x - 7 = -21 - 2x
<=> 7x = -14
<=> x = -2
\(20+7x-3x=4^5:4^3\)
\(20+4x=4^2\)
\(20+4x=16\)
\(4x=16-20\)
\(4x=-4\)
\(x=-1\)
Vậy \(x=-1\)
\(20+7x-3x=4^5:4^3\)
\(\Rightarrow\) \(20+4x=4^2\)
\(\Rightarrow\) \(20+4x=16\)
\(\Rightarrow\) \(4x=16-20\)
\(\Rightarrow\) \(4x=-4\)
\(\Rightarrow\) \(x=-1\)
a) 5x - x = 40 + 16
4x = 56
x = 14
b) -12 + 20 = 5x - x
8 = 4x
x = 2
c) 7x - 3x = 20 + 4
4x = 24
x=6
a) 5x-16=40+x
<=> 4x = 56
<=> x = 14
b) -12+x=5x-20
<=> 4x = 8
<=> x = 2
c) 7x-4=20+3x
<=> 4x = 24
<=> x = 6
1) 3x - 6= 5x + 2
5x - 3x = -6 - 2
2x = -8
x = -4
2) 15 - x = 4x - 5
4x + x = 15 + 5
5x = 20
x = 4
Tương tự như trên
1) 3x - 6 = 5x + 2
=> 3x - 5x = 2 + 6
=> -2x = 8
=> x = -4
2) 15 - x = 4x - 5
=> 15 + 5 = 4x + x
=> 20 = 5x
=> x = 4
3) x - 15 = 6 + 4x
=> x - 4x = 6 + 15
=> -3x = 21
=> x = -7
4) -12 + x = 5x - 20
=> x - 5x = -20 + 12
=> -4x = -8
=> x = 2
5) 7x - 4 = 20 + 3x
=> 7x - 3x = 20 + 4
=> 4x = 24
=> x = 6
1) 3x- 6 = 5x + 2
5x - 3x = -6 - 2
2x = -8 => x = -4
Tương tự như trên
7x-4=20+3x
7x-4=3x+20
7x-4+4=3x+20+4
7x=3x+24
7x-3x=3x+24-3x
4x=24
x=24:4
x=6
Vậy x=6